Figures 12-17 from: Fritzén N (2011) On a new Dictyna species (Araneae, Dictynidae) from the northern Palaearctic confused with the East Siberian D. schmidti Kulczyński, 1926. ZooKeys 138: 93-108. https://doi.org/10.3897/zookeys.138.1849 - Marusik, Yuri; Fritzén, Niclas (Zenodo, 2011)
Figures 12-17 - Male prosoma of Dictyna palmgreni sp. n. 12–13 from Pallastunturi, Dictyna schmidti 14–15 from Yakutia and Dictyna major 16–17 from Pyhtää 12, 14, 16 lateral 13, 15, 17 frontal.